Migrações na América Latina e Caribe: o direito à seguridade social do imigrante no Brasil - Peretti, Marizete (2018)
The migratory wave, which has intensified in recent years in several countries in the world, including in Latin America, has been driven by the most diverse factors, including the facilities of globalization, makes the issue of migrations relevant from the point of view of workers' social protection in displacement, since many of them are unprotected in their rights when they leave their places of origin. Given this scenario, this research has the objective of analyzing the protection that the displaced migrant in Latin America and the Caribbean receives in terms of social security, especially with regard to the social security of the immigrant worker in Brazil. Specifically, in the first chapter, we analyze migrations in Latin America and the Caribbean, considering the world migratory movement and its contemporary aspects, especially with regard to immigration in Brazil. The second chapter examines the social rights of the immigrant in Brazil, especially the right to social security as a fundamental right of the immigrant and an integrated responsibility of the States. In the third chapter, it is examined the Brazilian normative framework on international cooperation on social security, especially the international agreements in force in the country, considering the rights acquired abroad by the migrant worker and the portability of funds and social security benefits in the country, and presenting contributions for the adoption of measures that support immigrant workers from Latin American and Caribbean countries. It is considered that the migrant on the move in Latin America and the Caribbean receives social protection, especially with regard to the portability of funds and social security benefits in the case of Brazil, but that, nevertheless, still faces difficulties of the most varied when implementing their rights recognized by backed by international social security agreements.